Academic knowledge of arts in the Colombian public school (1800-1850) - Cárdenas, Óscar Leonardo; Cárdenas, Marco Tulio (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Within the framework of an archeo-genealogical approach, the present article has the purpose of exploring the historical conditions that allowed the emergence of knowledge of arts in the Colombian public school, materialized in school subjects such as drawing, singing and music, during the first half of the 19th century. Under this view, its genesis, purpose, and functioning are tracked, which were used as a discipline technology to complement the schooling and public instruction processes and the establishment of singular and standardized school individuals in accordance with the disciplinary rationality established in that moment. To achieve this objective, the researcher explored in the documentary archive of that period those vestiges related to the knowledge of the arts and to power relations that allowed their emergence.